Comparison of autoantibody‐positive and autoantibody‐negative pediatric participants enrolled in the T1D Exchange clinic registry (在1型糖尿病交流中心临床登记的自身抗体阳性与自身抗体阴性的儿科参与者的比较). (26th April 2013) - Gerard‐Gonzalez, Andrea; Gitelman, Stephen E.; Cheng, Peiyao; Dubose, Stephanie N.; Miller, Kellee M.; Olson, Beth A.; Redondo, Maria J.; Steck, Andrea K.; Beck, Roy W.
Abstract Objective To compare characteristics of autoantibody (aAb)‐positive and ‐negative cases of type 1 diabetes (T1D) <18 years old in the T1D Exchange clinic registry. Methods An aAb‐positive status (n = 6239) required at least one of the aAbs to be positive; an aAb‐negative status (n = 485) required negative results on testing of at least two different aAbs. Results The percentage of males was higher (58% vs 51%; P = 0.002) and total daily insulin dose lower (P = 0.003) in aAb‐negative compared with aAb‐positive groups, but both groups had similar distributions of race–ethnicity, diagnosis age, family history of T1D, ketoacidosis at diagnosis, body mass index at diagnosis and at most recent office visit, and current HbA1c. Conclusions Male gender and lower total daily insulin dose were more likely in aAb‐negative than aAb‐positive children with T1D, but no other distinguishing characteristics were identified. Further examination of characteristics of aAb‐negative cases may help characterize the heterogeneous nature of T1D.